Non-muslim awareness on halal elements pertaining to food products in Kota Kinabalu, Sabah / Adrian Sylvester Molius, Irene George Mojinggol and Jeoporda Clarret @ Clare Francis Brini - Molius, Adrian Sylvester (2013)
The aim of this paper is to determine the awareness of non-Muslims of Halal Elements Pertaining to Food Products in Kota Kinabalu, Sabah. A randomize sample of 200 respondents will be interviewed via structured questionnaires to gather information pertaining to their awareness, understanding and behavior towards Halal elements pertaining to food products. It is intended that this survey to be performed at Supermarkets in and around Kota Kinabalu areas. The results of this study suggest that non-Muslim consumers are not aware of Halal elements pertaining to food product in Kota Kinabalu. The research used a quantitative method to analyze 200 non-Muslim respondents in the Kota Kinabalu only. The practical implications encompass to food policy decision makers and food marketers who might pursue strategies in their distribution and communication efforts which target the growing Halal food market segments among non-Muslims. Disseminations of information play an important role in making non-Muslims improve their understanding of Halal elements pertaining to food products.